Syngamus trachea in free-ranging white stork (Ciconia ciconia) nestlings in Switzerland - Seraina L. Meister; Christian Wenker; Fabia Wyss; Irene Zühlke; Inês Berenguer Veiga; Walter U. Basso (International Journal for Parasitology: Parasites and Wildlife, 2022)
Syngamosis is a disease caused by the strongylid nematode Syngamus trachea, which infects the respiratory tract of various bird species around the world. The parasite appears to be harmful for a wide variety of avian orders, occasionally leading to a fatal outcome, particularly in young birds.The aim of this study was to examine the parasitic fauna in deceased or euthanized, free-ranging white storks nesting at the Zoo Basel in 2019 and 2020; and to assess the extent to which these parasites contributed to the wild birds' death.In five out of 24 necropsied white storks, an infection with S. trachea was diagnosed based on morphological analysis of adult nematode stages and eggs, in combination with PCR amplification and sequencing of DNA extracted from female worms. The main pathological changes affected the white storks’ respiratory tract and a mixed cell tracheitis was diagnosed in the histopathological examination of three of the five infected birds. Some birds displayed additional lesions compatible with syngamosis, namely partially degenerated parasitic structures with concurrent granulomatous inflammation in the lung and multifocal acute hemorrhages in the bronchi and parabronchi. Coprological examinations (fecal flotation technique, fecal sedimentation technique, sodium acetate acetic acid formalin procedure and Ziehl-Neelsen staining) from the intestinal content as well as a PCR for Toxoplasma gondii on brain, lung, heart, liver, and spleen tissue yielded negative results in all examined individuals. In the absence of further major pathological findings, S. trachea was assumed to have significantly contributed to the death of the infected birds.